SISTEM INFORMASI MANAJEMEN DALAM PENGELOLAAN DATA DI MTS ISLAMIYAH SUNGGAL - Eka Satya; Muhammad Fadhli (STKIP Pesisir Selatan, 2026)
The advancement of information technology has prompted educational institutions to strengthen the utilization of Management Information Systems (MIS) as an essential tool for enhancing the efficiency of data management. The availability of accurate, well-organized, and easily accessible data plays a crucial role in supporting administrative functions and facilitating informed decision-making within educational institutions. This study seeks to examine the implementation of a Management Information System in managing data at MTs Islamiyah Sunggal, with particular attention to data accuracy, the use of information in decision-making, and the system’s flexibility and accessibility. A qualitative descriptive method was adopted in this research. Data were gathered through direct observation, semi-structured interviews, and document analysis involving the principal, school operator, and teachers as research participants. The results reveal that MTs Islamiyah Sunggal has integrated several Management Information System applications, including EMIS, EMIS GTK, Madrasah Digital Report (RDM), Student Verification, Teacher Verification, and ERKAM, to facilitate institutional data management. Data accuracy is maintained through a systematic verification process based on official documents before information is entered into the system. The processed data subsequently serve as the primary basis for policy formulation, allowing school management to make more appropriate and evidence-based decisions.